2014
DOI: 10.1093/ejcts/ezu013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the Ross operation: an 18-year single institutional experience

Abstract: The RO was associated with excellent long-term survival and low incidence of reoperations up to 15 years. Male patients with AI and dilated annulus are at increased risk for late insufficiency and root dilatation. Fresh decellularized allografts presented the best results for reconstruction of the right ventricular outflow tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 22 publications
3
55
0
3
Order By: Relevance
“…In fact, a systematic review and meta‐analysis of hemodynamic outcomes reported the Ross procedure to be associated with a lower mean aortic gradient and demonstrated no difference in the incidence of severe aortic regurgitation compared to conventional AVR . Excess long‐term overall and cardiac‐related mortality have also been explained by patient‐prosthesis mismatch which appears to be reduced in patients undergoing the Ross procedure …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a systematic review and meta‐analysis of hemodynamic outcomes reported the Ross procedure to be associated with a lower mean aortic gradient and demonstrated no difference in the incidence of severe aortic regurgitation compared to conventional AVR . Excess long‐term overall and cardiac‐related mortality have also been explained by patient‐prosthesis mismatch which appears to be reduced in patients undergoing the Ross procedure …”
Section: Discussionmentioning
confidence: 99%
“…overall and cardiac-related mortality have also been explained by patient-prosthesis mismatch which appears to be reduced in patients undergoing the Ross procedure. [23][24][25]…”
mentioning
confidence: 99%
“…Возможно, эта точка (возраст 35 лет) может иметь некое прогнос-тическое значение для взрослых пациентов. В 2014 г. опубликовали результаты анализа еще од-ного центра, имеющего 20-летний опыт операции Рос-са (414 взрослых пациентов): госпитальная смертность 2,7%, выживаемость к 15-му году 89,3% (что соответс-твовало тренду популяции), а свобода от повторных операций к 15-му году была 90,7 и 92,5% в отношении гомографта и аутографта соответственно [14]. Это так-же согласуется с результатами еще одного центра, име-ющего 20-летний опыт выполнения операции Росса: госпитальная летальность 1,6% и общая летальность со-поставима с таковой в популяции в целом [15].…”
Section: Original Articlesunclassified
“…Clinical studies of decellularized aortic valve allografts showed stable structural integrity, low rate of calcification and adequate haemodynamics in the short to medium term (da Costa et al ., 2010). Up to 6 years’ follow‐up, SDS decellularized pulmonary allografts were associated with greater freedom from reoperations compared to conventional cryopreserved allografts (da Costa et al ., 2014). In Germany, the Haverich group have reported on the early results of fresh pulmonary allografts decellularized using 0.5% ( w / v ) sodium deoxycholate and 0.5% ( w / v ) SDS in children and young adults (Cebotari et al ., 2011; Neumann et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%